Gestational trophoblastic disease in hospital USM : a retrospective review - Narayanan, Dharmaraja (2016)
Introduction- Gestational trophoblastic disease (GTD) forms a group of disorders spanning the conditions of complete and partial molar pregnancies through to the malignant conditions of invasive mole, choriocarcinoma and the very rare placental site trophoblastic tumour (PSIT). The World Health Organization classification divides Trophoblastic Disease into the Pre malignant condition which is Partial Hydratirfonn moles, Complete hydatidiform moles and malignant condition such as Persistant Trophoblastic Disease, Invasive Mole, Choriocarcinoma, Placental Site Tumours. Molar pregnancies can be subdivided into complete (CM) and partial moles (PM) based on genetic and histopathological features. GTD is a rare event in the Europe, with a calculated incidence of 1/714 live births. Objectives- To deteimine prevalence of different types of Gestational Trophoblastic diseases, assess the associated factors of malignant condition compared to pre malignant condition and to determine the outcome of the chemotherapy treatment for patient with GTD. Methodology - A retrospective review was conducted on all GTD cases over the 10 year period between January 2002 and December 2011. The diagnosis and staging was classified using FIGO anatomical staging (Appendix A) and had histopathological confirmation of the disease, data was compiled through a clinical research form for analysis and data analysis was carried out with SPSS version 22. Results - Total of 123 cases were diagnosed with GTD within ten years span, there were 98 cases of Benign form GTD and 25 cases of malignant form ofGTD. Among the benign form of GTD there were 53(43.1%) patients with partial hydatidiform mole and 45(36.6%) with complete hydatidiform mole diagnosed clinically and conformed by histopathological evaluation. Malignant form of GTD accounted for total of 25(20.3%) patients, among which persistant trophoblastic disease (PTD) consist of 22 patients (17.9%) and 3(2.4%) patients with choriocarcinoma Among the associated factors of malignant disease studied was age, ethnicity, pre treatment hCG level, parity, child birth spacing, size of the uterus, size of molar tissue, history of molar pregnancy, previous usage of oral contraceptive pills and presence of thecal luthean cyst. Among the risk factors, age was strongly associated with malignant GTD, it was noted that with increase in every year of age the odds of developing malignant GTD was increased by 5%, The outcome of two major treatment group namely MTX regimen and EMACO regimen was studied, total of 22 patients received MTX as a single agent therapy, all of them were diagnosed with PTD and 19 patients had FIGO stage I disease and one patient with FIGO stage II disease and each one patients in stage III and stage IV disease, the patients in stage II and Ill needed second line chemotherapy with Actinomycin D and achieved full recovery, 19 patients in stage I received single agent MTX and complete recovery was achieved in 12 patients resulting in a success rate of 63% when used a single agent in stage I disease. There were 7 patients with stage I disease who failed to achieve satisfactory response with MTX alone and eventually requiring Actinomycin D (37%) achieved complete recovery from the disease. In this study 3 patients received EMA-CO regime as treatment, all of them were diagnosed with choriocarcinoma, two patients had stage I disease. One of them had hysterectomydone prior to treatment with EMA-CO and another received only EMA-CO after evacuation. Another one patient had stage IV disease with brain and liver metastasis, she was primarily started on EMA-CO and eventually succumbed to death. The remaining 2 patient had complete remission after treatment with EMA-CO, The success rate of EMA-CO in high risk patients at our center remains good as seen in previous studies. Conclusion - In this study the was no major changes in term of the epidemiology of the disease, it was well within the generally accepted prevalence for GTD. Perhaps the one of the most interesting finding in this study was the associated risk factors to develop malignant disease, in this study factors which had high association were age, high parity, and long interval of last child birth. Most patients had FIGO stage I disease, the response to single agent MTX treatment achieved an acceptable outcome, while the rest of the patients who received second line therapy also had a complete recovery. Patients who were in stage II and III had complete recovery with EMA-CO regime.MTX remains as our frrst line treatment in low risk patients while the usage of Actinomycin also proved beneficial in cases of resistant. For the patients in high risk category this study supports the use of EMA-CO.